Analogies of phonon anomalies and electronic gap features in the infrared response of Sr14−xCaxCu24O41 and underdoped YBa2Cu3O6+x. (10th March 2023) - Adamus, Petr; Xu, Bing; Marsik, Premysl; Dubroka, Adam; Barabasová, Paulína; Růžičková, Hana; Puphal, Pascal; Pomjakushina, Ekaterina; Tallon, Jeffery L; Mathis, Yves-Laurent; Munzar, Dominik; Bernhard, Christian
Abstract: We present an experimental and theoretical study which compares the phonon anomalies and the electronic gap features in the infrared response of the weakly coupled two-leg-ladders in Sr 14 − x Ca x Cu24 O41 (SCCO) with those of the underdoped high- T c superconductor YBa2 Cu3 O 6 + x (YBCO) and thereby reveals some surprising analogies. Specifically, we present a phenomenological model that describes the anomalous doping- and temperature-dependence of some of the phonon features in the a -axis response (field along the rungs of the ladders) of SCCO. It assumes that the phonons are coupled to charge oscillations within the ladders. Their changes with decreasing temperature reveal the formation of a crystal (density wave) of hole pairs that are oriented along the rungs. We also discuss the analogy to a similar model that was previously used to explain the phonon anomalies and an electronic plasma mode in the c -axis response (field perpendicular to the CuO2 planes) of YBCO. We further confirm that an insulator-like pseudogap develops in the a -axis conductivity of SCCO which closely resembles that in the c -axis conductivity of YBCO. Most surprisingly, we find that the c -axis conductivity (field along the legs of the ladders) of SCCO is strikingly similar to the in-plane one (field parallel to the CuO2 planes) of YBCO. Notably, in both cases a dip feature develops in the normal state spectra that is connected with a spectral weight shift toward low frequencies and can thus be associated with precursor superconducting pairing correlations that are lacking macroscopic phase coherence. This SCCO–YBCO analogy indicates that collective degrees of freedom contribute to the low-energy response of underdoped high T c cuprates and it even suggests that the charges in the CuO2 planes tend to segregate forming quasi-one-dimensional structures similar to the two-leg ladders, as predicted for the stripe-scenario or certain intertwinned states.